A Sketch Grammar of Pondi - Barlow, Russell (ANU Press, 2020)
This book provides the first grammatical description of Pondi, a severely endangered language spoken by fewer than 300 people, almost all of whom live in a single village in the East Sepik Province of Papua New Guinea. Pondi is a non-Austronesian (i.e. Papuan) language, belonging to the Ulmapo branch of the Keram family. A Sketch Grammar of Pondi includes ethnographic information, with ample discussion of language vitality and endangerment. The grammatical description begins with phonetics and phonology, before turning to major and minor word classes. The description of nominal morphology focuses especially on Pondi's irregular number affixation and stem alternation, while the description of verbal morphology is largely concerned with aspect and mood suffixation. Syntax is discussed both at the level of the phrase and at the level of the clause. Topics in syntax, such as questions, commands, negation and conditionals are discussed. Following the grammatical description, there is a lexicon of over 600 Pondi words, presented both as a Pondi-to-English word list and as an English-to-Pondi finder list.